Renal hybrid oncocytic/chromophobe tumors - a review - Hes, Ondrej; Petersson, Fredrik; Kuroda, Naoto; Hora, Milan; Michal, Michal (Histology and histopathology, 2013)
Hybrid oncocytic/chromophobe tumors (HOCT) occur in three clinico-pathologic situations; (1) sporadically, (2) in association with renal oncocytomatosis and (3) in patients with Birt-Hogg-Dubé syndrome (BHD). There are no specific clinical symptoms in patients with sporadic or HOCT associated with oncocytosis/oncocytomatosis. HOCT in patients with BHD are usually encountered on characteristic BHD clinicopathologic background. Sporadic HOCT are composed of neoplastic cells with eosinophilic oncocytic cytoplasm. Tumors are usually arranged in a solid-alveolar pattern. Some neoplastic cells may have a perinuclear halo, no raisinoid nuclei are present. HOCT occurring in patients with oncocytomatosis are morphologically identical to sporadic HOCT. HOCT in BHD frequently display 3 morphologic patterns, either in isolation or in combination; (1) An admixture of areas typical of RO and CHRCC, respectively, (2) Scattered chromophobe cells in the background of a typical RO, (3) Large eosinophilic cells with intracytoplasmic vacuoles. The immunohistochemical profiles of HOCT in all clinicopathologic and morphologic groups differ slightly. The majority of tumors express parvalbumin, antimitochondrial antigen and CK 7. CD117 is invariably positive. HOCT show significant molecular genetic heterogeneity. The highest degree of variability in numerical chromosomal changes is present in sporadic HOCT. HOCT in the setting of oncocytomatosis have revealed a lesser degree of variability in the chromosomal numerical aberrations. HOCT in patients with BHD display FLCN gene mutations, which are absent in the other groups. HOCT (all three clinicopathologic groups) seem to behave indolently, as no evidence of aggressive behavior has been documented. However, no report with follow up longer than 10 years has been published.
Keywords: mutace; eozinofily; Kidney; diferenciální diagnóza; Birt-Hogg-Dube Syndrome; Immunohistochemistry; Adenoma, Oxyphilic; oxyfilní adenom; lidé; Birtův-Hoggův-Dubeův syndrom; karcinom z renálních buněk; Mutation; Eosinophils; imunohistochemie; Diagnosis, Differential; prognóza; Kidney Neoplasms; Carcinoma, Renal Cell; protoonkogenní proteiny c-kit; progrese nemoci; chromozomální aberace; Disease Progression; Proto-Oncogene Proteins c-kit; Prognosis; nádory ledvin; ledviny; Chromosome Aberrations; Humans